Oil Palm Boom and Land-Use Dynamics in Indonesia: The Role of Policies and Socioeconomic Factors - Marcel Gatto; Meike Wollni; Matin Qaim (GOEDOC, Dokumenten- und Publikationsserver der Georg-August-Universität, 2014)
We investigate land-use dynamics in Jambi, Sumatra, one of the hotspots of Indonesia' recent oil palm boom. Data from a structured village survey are used to analyze the role of socioeconomic and policy factors. Oil palm is partly grown on large plantations, but smallholders are also involved significantly. We find that, in spite of significant oil palm expansion, rubber remains the dominant crop. Most of the oil palm growth takes place on previous fallow and rubber land. Oil palm has not been a major driver of deforestation. Much of the forest in Jambi was cleared more than 20 years ago, and rubber was an established cash crop long before the oil palm boom started. However, oil palm growth occurs in locations with ongoing logging activities, so indirect effects on deforestation are likely. The government's transmigration program of the 1980s and 1990s was instrumental for the start and spread of oil palm in Jambi. Some autochthonous villages have adopted oil palm, but adoption started later compared to migrants from Java, and it happens at a slower pace. While the transmigration program benefited many of the participating families, it has contributed to the risk of unequal socioeconomic developments in Jambi.
urn:nbn:de:gbv:7-webdoc-3938-6
Keywords: 330; oil palm; land-use change; deforestation; socioeconomic factors; Indonesia; government policy; Palme; Pflanzenbau; Landnutzung; Entwaldung; Arbeitskräftelenkung; Sumatra; Indonesien